Effects of epidural anesthesia on postpartum maternity blues and fatigue and its relation to changes in oxytocin. Issue 3 (19th January 2021) - Shishido, Eri; Shuo, Takuya; Shinohara, Kazuyuki; Horiuchi, Shigeko
Abstract: Aims: This study aimed to clarify (a) the association of the delivery mode (i.e., epidural anesthesia or no epidural) with women's changes in longitudinal salivary oxytocin (OT) levels from late pregnancy to early postpartum, and (b) the association of these changes with postpartum maternity blues (MB) and fatigue. Methods: We used a longitudinal observational design. We performed measurements of the saliva samples at four measurement points: (a) 36–37 gestational weeks, (b) 38–39 gestational weeks, (c) 1–2 days after birth, and (d) 4–5 days after birth. The inclusion criterion was low‐risk primiparous women who were planning to have vaginal delivery. We used Stein's MB scale to evaluate postpartum data and a visual analog scale to examine "postpartum fatigue". We determined the association between the MB/fatigue scores and the changes in the OT levels by Spearman's rank correlation coefficient. Results: There were 29 women who delivered with epidural anesthesia and 29 women who did not. A significantly higher mean salivary OT level was observed in the women with epidural anesthesia at 1–2 days after birth than at 36–37 gestational weeks. The mean OT level at 4–5 days postpartum was significantly lower than that at 1–2 days postpartum. The correlation of the MB score with the salivary OT level at 4–5 days postpartum was ρ = −0.33, p  = .01. Conclusions: Early postpartum OT level decreased with epidural anesthesia and showed a negative correlation with postpartum MB and fatigue. Healthcare providers should recognize that women who had epidural anesthesia need specific supportive care.